Standardization of Raman spectra using variable penalty dynamic time warping. Issue 30 (13th July 2021) - Xu, Qingyu; Chen, Hongju; Ye, Shaoqing; Zeng, Yongming; Lu, Hongmei; Zhang, Zhimin
Abstract : The RS-VPdtw method can synchronize the nonlinear displacement between spectra acquired with different spectrometers. Abstract : Raman spectroscopy can provide structural fingerprints to identify molecules by means of spectral library searching. However, it is difficult to share the spectral library between different Raman spectrometers because of the nonlinear displacement in Raman shift. In this study, we propose a Raman spectra Standardization method using Variable Penalty dynamic time warping (RS-VPdtw), which can synchronize the nonlinear displacement between spectra acquired with different spectrometers. We have compared the standardization performance of RS-VPdtw and MWFFT on the spectra of 13 real samples acquired with 6 different spectrometers. The mean spectral similarity of RS-VPdtw and MWFFT increased from 0.79 to 0.97 and 0.91 respectively. Results show that RS-VPdtw is significantly better than MWFFT in Raman spectra standardization. The Raman spectra acquired with different spectrometers can be standardized by RS-VPdtw to search the same spectral library, which can avoid the time-consuming and labor-intensive reestablishment of spectral libraries for different spectrometers. This means that RS-VPdtw is a promising and valuable method to solve the spectra standardization problem in large-scale applications of Raman spectroscopy.